Achieving Functional Meta‐Devices by Generalized Meta‐Atom Model for Metasurfaces and Genetic Algorithm (Advanced Optical Materials 10/2024) - Chen, Jian; Ding, Wei; Shi, Yuan‐Cheng; Yao, Zhen‐Xu; Wu, Rui‐Xin (Advanced optical materials, 2024)
Meta‐Atom Model for Metasurfaces By pixelating the unit cell of metasurfaces, the machine‐learning‐based meta‐atom model was developed. The model can cover the entire pixel space and simulate any potential meta‐atoms operating at any polarization. In article number 2302255, Rui‐Xin Wu and co‐workers applied the model to design different types of functional meta‐devices, including the reflective and the transmissive ones implemented by one or multiple metasurfaces, and a metasurface with one or more meta‐atoms. The designs were verified through simulations and experiments. The model significantly improves the design efficiency of the meta‐devices.